Fiber optical network design problems: A case for Turkey. (September 2016) - Yazar, Başak; Arslan, Okan; Karaşan, Oya Ekin; Kara, Bahar Y.
Abstract: In this paper, we consider problems originating from one of the largest Internet service providers operating in Turkey. The company mainly faces two different design problems: the green field design (area with no Internet access) and the copper field re-design (area with limited access over copper networks). In the green field design problem, the aim is to design a least cost fiber optical network that will provide high bandwidth Internet access from a given central station to a set of aggregated demand nodes. Such an access can be provided either directly by installing fibers or indirectly by utilizing passive splitters. Insertion loss, bandwidth level and distance limitations should simultaneously be considered in order to provide a least cost design to enable the required service level. In the re-design of the copper field application, the aim is to improve the current service level by augmenting the network with fiber optical wires, specifically by adding cabinets to copper rings in the existing infrastructure and by constructing direct fiber links from cabinets to distant demand nodes. Mathematical models are constructed for both problem specifications. Extensive computational results based on realistic data from Kartal (45 nodes) and Bakırköy (74 nodes) districts in Istanbul show that the proposed models are viable exact solution methodologies for moderate dimensions. Abstract : Highlights: We consider problems originating from one of the largest Turkish Internet service providers. The first problem is the green field design (area with no Internet access). The second problem is the copper field re-design (area with limited access over copper networks). Insertion loss, bandwidth level and distance limitations are considered to provide a least cost design. Extensive computational results based on data from districts in Istanbul are carried out.